PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBASIS POWERPOINT INTERAKTIF UNTUK SISWA KELAS V SEKOLAH DASAR NEGERI GONDOLAYU - Fida Amalia Buana Putri; Shanta Rezkita (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
Based on the necessary with the teacher, it is concluded that teachers need information technology (IT) based on learning media in the teaching and learning process. The main purpose of this study is to know about the research procedure, to know about the quality of the media that developed, and the expert's respond. This study is a Research and Development (R&D). The on Â procedure of the procedure uses 9 steps, including 1)Potentials and problems, 2)Data collection, 3)Product design, 4)Design validation, 5)Design revision, 6)Product try-out, 7)Product revision, 8)Application try-out, 9)Product revision until the desired products interactive powerpoint learning media are complete. The result of the study showed that the media were appropriate to be implemented. This showed from media experts of the validation result that average score 3,34 with a very good category. Material expert student's that average score 3,40 with very good category and from linguists expert result that average score 3,22 with the good category. Next, the average validation score of the teacher is 3,62 with a very good category and peers of the validation result that average score 3,44 with a very good category. The last response of the students in applications try-out responses that average score 92,75 with a very good category.Â